Why don't labor and capital flow between young and old countries? - Lena Calahorrano; Philipp an de Meulen (Philipps-University Marburg, Faculty of Business Administration and Economics, 2009)
In this paper we investigate the twofold effect of demographics on international factor flows in a model with endogenous policy constraints on both foreign direct investment and migration. Factor price differences between industrialized and developing countries create economic incentives for migration to developed countries and for capital flows to less developed countries. However, political barriers to immigration in developed countries and expropriation risks in developing countries impede labor and capital flows. Using a political economy approach that takes into account different generations' conflicting attitudes towards immigration and expropriation, we explore how these policy restrictions interact. We find that, in the presence of mobility constraints, larger demographic differences between countries need not result in an increase of factor flows.
Keywords: D78; F21; F22; J10; 330; Demographic Change; Political Economy; Migration; Foreign Direct Investment